Exploring the Communal Pathogenesis, Ferroptosis Mechanism, and Potential Therapeutic Targets of Dilated Cardiomyopathy and Hypertrophic Cardiomyopathy via a Microarray Data Analysis - Wang, Zuoxiang; Xia, Qingyue; Su, Wenxing; Cao, Mingqiang; Sun, Yunjuan; Zhang, Mingyang; Chen, Weixiang; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiomyopathies is a heterogeneous group of heart diseases which could gradually cause severe heart failure, and its two main types are dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM). the independent and communal biological mechanisms of the two types still far from elucidated. Meanwhile, Ferroptosis is a non-apoptotic form of cell death which have been proved to be associated with cardiomyopathies, but the concrete interaction remains unclear. Hence, this study explored Pathogenesis and Ferroptosis Mechanism of HCM and DCM via bioinformatic analysis. Methods: six datasets were downloaded from the Gene Expression Omnibus (GEO) database based on inclusion/exclusion criteria. After screening the DEGs and hub genes of HCM and DCM, subsequent analysis were performed, such as functional annotation, co-expression, validation, and TF-mRNA-miRNA regulatory network construction. In addition, ferroptosis-related DEGs were also identified and verified in HCM and DCM. Results: We found 171 independent DEGs of HCM mainly enriched in regulation of ERK1 and ERK2 cascade, and 171 independent DEGs of DCM significantly involved in cell adhesion. Meanwhile, 32 communal DEGs (26 upregulated genes and 6 downregulated genes) and three hub genes (POSTN, IGFBP5 and FMOD) were determined between HCM and DCM, and function annotation of these genes highlighted the important position of the growth hormone in HCM and DCM. Moreover, we found ATF3, LPCAT3 and SLC1A5 as ferroptosis- related genes in HCM, and STAT3 as Ferroptosis- related genes in DCM. Conclusion: The independent and communal DEGs contributes to uncover potential distinct and common mechanism of HCM and DCM, and ferroptosis-related genes could provide us a novel exploring direction. In addition, three hub genes could be potential biomarkers or therapy targets for cardiomyopathy.